Working Framework and Connotation of Building Block Methodology for Environmental Flow Assessment - DING Wei; LAN Lin; MIAO Lingzhan; HUANG Yuwei; SU Yongtao; SHAO Ningzi; HOU Jun (Renmin Zhujiang)
The existing method for environmental flow assessment in China only focuses on specific target species.Considering this deficiency,a holistic approach,i.e.,building block methodology (BBM),is elaborately introduced for evaluating environmental flow.According to the scientific basis and actual needs,this method accurately divides the research objects and influencing factors in the whole study area into different “blocks” and then explores the relationship between each “block” of influencing factors and each research object.Finally,a reasonable environmental flow scheme is drawn up for the whole study area.Its working steps are mainly divided into three parts:Before the seminar,experts collect the basic data;during the seminar,experts from various disciplines explain the collected data and reach a consensus on the recommended environmental flow;after the seminar,they develop the flow modification scheme and the monitoring plan.With the application examples of Sri Ram Sagar Reservoir in India and Daleeleva River in Norway,we analyze the characteristics and shortcomings of this method.It is revealed that this method can better ensure the ecological value and service value of rivers in the process of determining environmental flow and can provide a reference for its application in China.